Empirical modeling of plasma sheet pressure and three‐dimensional force‐balanced magnetospheric magnetic field structure: 2. Modeling. Issue 10 (31st October 2013) - Yue, Chao; Wang, Chih‐Ping; Zaharia, Sorin G.; Xing, Xiaoyan; Lyons, Larry
Abstract [1] The magnetic field configuration is crucial to plasma sheet dynamics and magnetosphere‐ionosphere coupling. In this study we established 3‐D force‐balanced magnetic fields and investigated configuration changes with Kp and solar wind dynamic pressure (PSW). Pressure distributions from the empirical model developed in Wang et al. (2013) were used for obtaining the force‐balanced field. Based on our model results, we found that (1) higher PSW mainly enhances pressure in the tail plasma sheet, while larger convection during higher Kp drives plasma sheet further earthward, resulting in a pressure increase closer to the Earth; (2) comparing with the magnetic field changes due to increasing PSW, the Kp associated pressure enhancement causes the azimuthal current density (Jϕ) peak and field‐aligned currents (FACs) to move deeper earthward, the magnetic field to decrease further near Earth but increase more in the tail, and field lines to stretch more significantly; (3) as Kp and PSW change, the whole plasma sheet remains stable to interchange instability but may be ballooning unstable in the midnight region at X between −15 and −10 RE; (4) the force‐balanced configurations are characteristically different from the non‐force‐balanced Tsyganenko 89 (T89) magnetic field. A region of positive dBz/dz in the near‐Earth region, which has been observed, is seen in our field but not in T89. On the other hand, a local equatorial Bz minimum is predicted by T89 but not by our model. Jφ bifurcation appears in the near‐Earth region as a result of our Jφ configuration being approximately aligned with field lines, while the T89 Jφ everywhere decreases monotonically with increasing Z by construction.